Municipal environmental management and regional conservation in eastern Amazon: perceived performance by public agents in the Pará state, Brazil - Silva, Benedito Evandro Barros da; Azevedo-Ramos , Claudia; Farias, Hilder André Bezerra (Sustainability in Debate, 2022)
Public agents play a key role in municipal environmental management (MEM) under decentralised regimes. This study aimed to evaluate the MEM through the combined perception of municipal agents and the municipal performance previously calculated by secondary data in Pará, Brazil. A questionnaire with a 5-point Likert scale was applied to environmental agents. The respondents (n = 75) from 53 municipalities were divided into poorly performing and well-performing municipalities. The perception of agents from poorly performing municipalities was more optimistic than shown by empirical data. Agents from well-performing municipalities prioritised “economic issues” as significant threats to management over the “institutional capacity” chosen by the other group, indicating a broader view of the reality. As the perception over land-use practices was vital to differentiate the agents from different groups, we concluded for the use of mixed monitoring methods and feedback information for agents for a better MEM, focusing on five variables (Rural environmental register – CAR, in Portuguese acronym; degraded area; deforested area; rural credit; and abandoned pasture) that differentiated the municipalities.